2024
DOI: 10.1007/s00401-024-02696-z
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of β-amyloid, Tau and α-synuclein to blood–brain barrier damage in neurodegenerative disorders

Ying-Chieh Wu,
Tizibt Ashine Bogale,
Jari Koistinaho
et al.

Abstract: Central nervous system (CNS) accumulation of fibrillary deposits made of Amyloid β (Aβ), hyperphosphorylated Tau or α-synuclein (α-syn), present either alone or in the form of mixed pathology, characterizes the most common neurodegenerative diseases (NDDs) as well as the aging brain. Compelling evidence supports that acute neurological disorders, such as traumatic brain injury (TBI) and stroke, are also accompanied by increased deposition of toxic Aβ, Tau and α-syn species. While the contribution of these path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…CAMs are a distinct population of brain resident macrophages located within CNS interfaces, which include the perivascular spaces (perivascular macrophages, PVMs), the leptomeninges (meningeal macrophages, MMs), and the choroid plexus (choroid plexus macrophages, ChPM) and are identified in human and mouse brain as CD163 + and CD206 + cells, respectively [ 12 ]. Recent studies have indicated that CAMs are involved in a wide variety of pathological states [ 8 , 9 , 23 , 48 ]. Their main functions, as described to date, include regulation of blood–brain barrier (BBB) integrity and cerebrospinal fluid (CSF) dynamics, phagocytosis of blood-borne pathogens, and control of leukocyte migration [ 10 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CAMs are a distinct population of brain resident macrophages located within CNS interfaces, which include the perivascular spaces (perivascular macrophages, PVMs), the leptomeninges (meningeal macrophages, MMs), and the choroid plexus (choroid plexus macrophages, ChPM) and are identified in human and mouse brain as CD163 + and CD206 + cells, respectively [ 12 ]. Recent studies have indicated that CAMs are involved in a wide variety of pathological states [ 8 , 9 , 23 , 48 ]. Their main functions, as described to date, include regulation of blood–brain barrier (BBB) integrity and cerebrospinal fluid (CSF) dynamics, phagocytosis of blood-borne pathogens, and control of leukocyte migration [ 10 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cellular antioxidant system, composed of superoxide dismutase (SOD), catalase (CAT), peroxidase, and reduced glutathione (GSH), acts as a free radical scavenger, and neurodegeneration is promoted due to an imbalance in the defensive actions of antioxidants and overproduction of ROS. , Moreover, neuroinflammation, which is initially crucial for stimulating tissue repair and removing the brain’s cellular waste, could be a significant key factor in the pathogenesis and progression of various NDs in cases of persistence due to genetic mutations, trauma, and infection, which play their roles via proinflammatory agent release, including interleukin-6 (IL-6) and immune cell activation, leading to neuronal dysfunction and destruction. In fact, the engagement and overactivity of microglia and astrocytes in neuroinflammatory responses might be responsible for the pathogenesis of neurodegenerative diseases, especially Alzheimer’s disease, in which microglia play a vital role in responding to Aβ aggregation. The major NDs include Alzheimer’s disease (AD), Parkinson’s disease (PD), ataxia, Huntington’s disease (HD), motor neuron disease, multiple system atrophy, and progressive supranuclear palsy, in which the main causes are reported to be the accumulation of amyloid β (Aβ), Tau, and α-synuclein in the form of insoluble fibrillary deposits with β-sheet structure in the brain of patients. , According to the Global Burden of Disease (GBD) study, a variety of conditions, including AD, PD, multiple sclerosis (MS), and epilepsy, as well as headache disorders such as migraine, tension-type headache, and medication-overuse headache, collectively contribute to 3% of the GBD. The top 50 causes of disability-adjusted life years (DALYs) include dementia, epilepsy, migraine, and stroke…”
Section: Introductionmentioning
confidence: 99%
“…disease (PD), ataxia, Huntington's disease (HD), motor neuron disease, multiple system atrophy, and progressive supranuclear palsy, in which the main causes are reported to be the accumulation of amyloid β (Aβ), Tau, and α-synuclein in the form of insoluble fibrillary deposits with β-sheet structure in the brain of patients. 11,12 According to the Global Burden of Disease (GBD) study, a variety of conditions, including AD, PD, multiple sclerosis (MS), and epilepsy, as well as headache disorders such as migraine, tension-type headache, and medication-overuse headache, collectively contribute to 3% of the GBD. The top 50 causes of disability-adjusted life years (DALYs) include dementia, epilepsy, migraine, and stroke.…”
Section: Introductionmentioning
confidence: 99%